(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the concept of ‘human’ in English, Russian, and Uzbek from a cross-linguistic and cultural perspective. While extensive research exists on anthropocentric concepts within individual languages, there is a lack of comparative studies exploring how different linguistic and cultural traditions conceptualize ‘human.’ Addressing this gap, the study investigates how language encodes cultural perceptions of human nature, identity, and societal roles. Using a linguocultural approach, the research employs semantic analysis, corpus-based methods, and comparative examination of dictionary definitions, literary texts, and proverbs. This methodology allows for identifying both universal and culturally specific aspects of the ‘human’ concept in the selected languages. Findings indicate that while all three languages associate ‘human’ with intelligence, morality, and social interaction, key differences emerge. English tends to emphasize individualism and self-expression, Russian reflects collectivist ideals and spiritual dimensions, and Uzbek highlights communal values and ethical responsibilities. Metaphorical and idiomatic expressions further illustrate how cultural worldviews influence linguistic representations of humanity. These results provide valuable insights for cognitive linguistics, intercultural communication, and translation studies, demonstrating how language shapes and reflects cultural perspectives on human identity. The study underscores the importance of cross-linguistic research in understanding conceptual variations, contributing to broader discussions on language, thought, and culture.